SEKOLAH DREAMABLE : Sebuah Upaya Meningkatkan Kemandirian Anak Berkebutuhan Khusus (Studi Implementasi Program CSR PT Pertamina (Persero) Fuel Terminal Bandung Group) - Intan Lukfia Indriyani; Gokhan Gokhan; Rahadiyand Aditya; Geri Puspa Perdana; Anis Putri Isnaeni (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2020)
Education in Indonesia is still difficult for some segments such as ABK who have escaped maximum attention and management. Although there has been government assistance to provide access to education that is appropriate for every child through inclusive education. However, it still requires challenges, such as the lack of complete learning support facilities for ABK, expensive and distant schools, teachers who need knowledge about ABK, and others. Then the roles of various sectors are needed in efforts to fulfill disability rights. This study uses a qualitative descriptive approach that describes the implementation of CSR programs in handling ABK. This research was conducted at the Sekolah Dreamable located in Tegalluar village, Bojongsoang District, Bandung Regency, West Java. Data collection techniques using interview techniques and study documentation. The results of this study indicate that PT Pertamina (Persero) Fuel Terminal Bandung Group in CSR programs implementing at Sekolah Dreamablein Bojongsoang District, Bandung uses a combination program strategy pattern that combines centralized and decentralized program patterns. Where in planning, the program determination and implementation involves the participation of various stakeholders. As a form of implementation, CSR that has been carried out by PT Pertamina (Persero) Fuel Terminal Bandung Group not only consists of Charity such as complimentary books and school supplements but also Philanthropy such as School Development and the procurement of Homecare Cars, and Community Development through purchasing the capacity of Teachers and Special Needs.Keywords: Corporate Social Responsibility, ABK Handling, Inclusive Education